2002
DOI: 10.1097/00007632-200209010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Early Occupational Health Management of Patients with Back Pain

Abstract: The findings do not show a significant positive effect of an early intervention by occupational physicians on workers with low back pain. This might reflect the early phase of disability or the low intensity of the intervention resulting from overestimation of the physicians' compliance with the guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 30 publications
3
49
1
6
Order By: Relevance
“…The RTW case managers serve a range of duties in occupational rehabilitation, which include the following: (1) initial assessment of physical and functional rehabilitation, capability of the worker related to accommodations in the equipment and work environment; (2) job analysis and advice pertaining to job modifications; (3) further occupational rehabilitation counseling and job skill retraining; and (4) post-RTW monitoring and coordination [4]. The strategies directed at shortening sick leave and improving RTW successes have been examined and some have been verified via intensive multidisciplinary programs [8][9][10][11][12]. A clinical randomized trial on RTW of workers with musculoskeletal injuries showed that intensive training on work readiness significantly improved their preparedness to work, improved their own perceptions of health status, and decreased their level of anxiety [13].…”
Section: Introductionmentioning
confidence: 99%
“…The RTW case managers serve a range of duties in occupational rehabilitation, which include the following: (1) initial assessment of physical and functional rehabilitation, capability of the worker related to accommodations in the equipment and work environment; (2) job analysis and advice pertaining to job modifications; (3) further occupational rehabilitation counseling and job skill retraining; and (4) post-RTW monitoring and coordination [4]. The strategies directed at shortening sick leave and improving RTW successes have been examined and some have been verified via intensive multidisciplinary programs [8][9][10][11][12]. A clinical randomized trial on RTW of workers with musculoskeletal injuries showed that intensive training on work readiness significantly improved their preparedness to work, improved their own perceptions of health status, and decreased their level of anxiety [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous attempts to reduce absence due to LBP in occupational settings do not show any consistent positive effects, or any remarkable effect size. 'Back schools', lumbar supports, ergonomic interventions and risk factor modification have not yet demonstrated their effectiveness [3][4][5][6]. There is consensus that exercise is beneficial, but the effect size appears to be moderate [1,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have used the insurer-reported days absent as a readily available outcome measure [Dasinger et al, , 2000Krause et al, 1999;Fulton-Kehoe et al, 2000;Murphy and Courtney, 2000;Krause et al, 2001;Reville et al, 2001;Verbeek et al, 2002;Hogg-Johnson and Cole, 2003]. Although the administrative data are less expensive to collect, compared to self-reported days absent, questions exist as to the accuracy, cost, and utility of both measures Amick et al, 2000;Young et al, 2002;Wasiak et al, 2003].…”
Section: Introductionmentioning
confidence: 99%